Functions of Autobiographical Memory in Younger and Older Adults - Vranić, Andrea; Jelić, Margareta; Tonković, Mirjana (Frontiers in Psychology, 2018)
Functional approach to autobiographical memory (AM) posits its’ three broad functions: directive, self, and social. Although these functions are probably universal, life stages and gender variations are expected. This research builds on previous studies investigating the validity of Thinking About Life Experiences Questionnaire (TALE; Bluck & Alea, 2011). A sample of 365 adults (56% female, mean age 43.3yrs), divided in 2 age cohorts (young: 18-45yrs, old: 46-90yrs), used TALE, to rate their tendency of using AM for three different purposes, and measures of self-concept clarity, attachment in close relationships and time perspective. Confirmatory factor analysis of TALE confirmed the tripartite model of AM functions and further analysis showed partial factorial equivalence across age and gender groups. Young tend to use AM more for directing future behavior and social-bonding, while no age differences were found in the use of AM to serve self function. As for gender variations, women tend to use AM more for directing their behavior, while no other gender differences in the use of AM were found. TALE showed good internal consistency and convergent validity of the three subscales. The theory-driven hypotheses that individuals with low self-concept clarity would use AM more often to serve a self-function, those with higher levels of attachment anxiety would use AM more often to serve a social function, and those past-oriented would use memory more often for directive purpose, were all confirmed. Also confirmed was the notion of Past Negative Orientation to be more related to the directive use of AM than Past Positive Time Orientation. Limitations and future directions are discussed.